Grand expectations : the United States, 1945-1974 - Patterson, James T. (New York : Oxford University Press, 1996)
Beginning in 1945, America rocketed through a quarter-century of extraordinary economic growth, experiencing a boom that soared to unimaginable heights in the 1960s. It was a boom that produced a national euphoria, a time of grand expectations and an unprecedented faith in our government, in our leaders, and in the American dream, an optimistic spirit which would be shaken by events in the '60s and '70s, and particularly by the Vietnam War. Now, in this volume the author has written a work that weaves the major political, cultural, and economic events of the period into a portrait of America from 1945 through Watergate. He portrays the amazing growth after World War II, the great building boom epitomized by Levittown (the largest such development in history) and the baby boom (which exploded literally nine months after V-J Day), as well as the resultant buoyancy of spirit reflected in everything from streamlined toasters, to big, flashy cars, to the soaring, butterfly roof of TWA's airline terminal in New York. And he shows how this upbeat, can-do mood spurred grander and grander expectations as the era progressed. Of course, not all Americans shared in this economic growth, and an important thread running through the book is a depiction of the civil rights movement, from the Brown v. Board of Education decision, to the confrontations in Little Rock, Birmingham, and Selma, to the civil rights acts of 1964 and 1965. The author also shows how the Vietnam War, which provoked LBJ's growing credibility gap, vast defense spending that dangerously unsettled the economy, and increasingly angry protests, and a growing rights revolution triggered a backlash that widened hidden rifts in our society, rifts that divided along racial, class, and generational lines. And by Nixon's resignation, we find a national mood in stark contrast to the grand expectations of ten years earlier, one in which faith in our leaders and in the attainability of the American dream was becoming shaken.
August 1945 -- Veterans, ethnics, blacks, women -- Unions, liberals, and the state: stalemate -- Booms -- Grand expectations about the world -- Hardening of the Cold War, 1945-1948 -- Domestic politics: Truman's first term -- Red scares abroad and at home -- Korea -- Ike -- World affairs, 1953-1956 -- The biggest boom yet -- Mass consumer culture -- Race -- A center holds, more or less, 1957-1960 -- The polarized sixties: an overview -- The new frontier at home -- JFK and the world -- Lyndon Johnson and American liberalism -- A great society and the rise of rights-consciousness -- Escalation in Vietnam -- Rights, polarization, and backlash, 1966-1967 -- The most turbulent year: 1968 -- Rancor and Richard Nixon -- Nixon, Vietnam, and the world, 1969-1974 -- End of an era? : expectations amid Watergate and recession.
Includes bibliographical references (pages 791-802) and index.
Bancroft Prize, 1997.
Keywords: United States -- History -- 1945-; Social change -- United States -- History -- 20th century; United States -- Politics and government -- 20th century; United States -- Economic conditions -- 20th century; Economic history; Political science; Social change; United States; x; USA; Since 1900; United States -- History, 1945-1974.; History